1977
DOI: 10.1037/0022-3514.35.9.656
|View full text |Cite
|
Sign up to set email alerts
|

Social perception and interpersonal behavior: On the self-fulfilling nature of social stereotypes.

Abstract: This research concerns the self-fulfilling influences of social stereotypes on dyadic social interaction Conceptual analysis of the cognitive and behavioral consequences of stereotyping suggests that a perceiver's actions based upon stereotype-generated attributions about a specific target individual may cause the behavior of that individual to confirm the perceiver's initially erroneous attributions. A paradigmatic investigation of the behavioral confirmation of stereotypes involving physical attractiveness (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
637
6
12

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,134 publications
(679 citation statements)
references
References 42 publications
24
637
6
12
Order By: Relevance
“…Conversely, idealized intimates may be happier in their relationships because their partners treat them as special individuals, thereby encouraging intimates to live up to these idealized images (e.g., Snyder & Swann, 1978;Snyder, Tanke, & Berscheid, 1977). Also, if actors see their partners' behaviors through the rosy filters provided by their ideals, their inclination toward "attributional charity" might minimize the potential for overt conflict (e.g., Rusbult, Verette, Whitney, Slovik, & Lipkus, 1991).…”
Section: Is Love Blind? Positive Illusions and Relationship Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, idealized intimates may be happier in their relationships because their partners treat them as special individuals, thereby encouraging intimates to live up to these idealized images (e.g., Snyder & Swann, 1978;Snyder, Tanke, & Berscheid, 1977). Also, if actors see their partners' behaviors through the rosy filters provided by their ideals, their inclination toward "attributional charity" might minimize the potential for overt conflict (e.g., Rusbult, Verette, Whitney, Slovik, & Lipkus, 1991).…”
Section: Is Love Blind? Positive Illusions and Relationship Well-beingmentioning
confidence: 99%
“…In addition to providing constructive motivation, illusions may create resources of goodwill and generosity that prevent everyday hassles from turning into significant trivia (Holmes & Murray, in press). Intimates might even create elements of the idealized reality they perceive by treating their partners as special, unique individuals (e.g., Snyder & Swann, 1978;Snyder et al, 1977), In these ways, idealizing a partner may provide an effective buffer against the inevitable vicissitudes of time.…”
Section: Hidden Realities: a Sleeper Effect?mentioning
confidence: 99%
“…This design enabled us to present consistent stimuli across subjects and eliminate communication, but also limited the richness of each interaction. Photographs are often used to study the effects of physical attractiveness (Snyder, Tanke, & Berscheid, 1977;Marlowe, Schneider, & Nelson, 1997), though photographs may amplify (Ambady & Rosenthal, 1993) or curtail (McCall, 1997) attractiveness effects.…”
Section: Introductionmentioning
confidence: 99%
“…Milgram (2010a) felt that with the method people could experience "radical deformations" (p. 408) of self during social interactions mediated by a shadower's body that was vastly divergent from their own in terms of gender, ethnicity, age, social status, and so on. At the time of Milgram's cyranoid studies it was well known that people stereotype other individuals on the basis of their outward identity (e.g., Cantor & Mischel, 1979;Tajfel, Sheikh, & Gardner, 1964) and that people's behavior in many ways confirms the stereotypes held by others (e.g., Snyder, Tanke, & Berscheid, 1977), but experimental validations of these phenomena were largely, if not entirely, third-person in nature. So whereas the traditional literature showed that people stereotype (along with descriptions on the nature of stereotyping in various contexts),…”
Section: Milgram's Cyranoid Methodsmentioning
confidence: 99%